2005
DOI: 10.1002/pros.20219
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for advanced glycation end products (RAGE) and its ligand, amphoterin are overexpressed and associated with prostate cancer development

Abstract: The AGE-RAGE interaction is important in prostate cancer development, and inhibition of this interaction has potential as a new molecular target for cancer therapy or prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
168
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(177 citation statements)
references
References 20 publications
7
168
0
2
Order By: Relevance
“…Over-expression of HMGB1 is reported in prostate cancer cells (50,51) and depletion of HMGB1 expression induces apoptosis in prostate cancer cells (52). HMGB1 is a potent attractant for inflammatory cells including neutrophils, monocytes and macrophages as well as inducer of pro-inflammatory cytokines such as TNF-α, IL-1α, IL-1β, IL-6 and IL-8 production (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Over-expression of HMGB1 is reported in prostate cancer cells (50,51) and depletion of HMGB1 expression induces apoptosis in prostate cancer cells (52). HMGB1 is a potent attractant for inflammatory cells including neutrophils, monocytes and macrophages as well as inducer of pro-inflammatory cytokines such as TNF-α, IL-1α, IL-1β, IL-6 and IL-8 production (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…2,34 AGEs cell surface receptor (RAGE) is an immunoglobulin superfamily member, whose overexpression has been recently associated with prostate cancer (PCa) development either in vivo or in vitro. 35 Therefore, the overexpression of RAGE on LNCaP cells may potentiate the antiproliferative effect of free MG, via MG/AGE-RAGE complexes, thus contributing to the observed reduction in cell proliferation in the presence of GI mRNA levels likely non-sufficient to produce enough protein. Similarly, it is likely that the high expression levels of GII gene, occurring simultaneously with the high GI gene expression, may be the consequence of a major cell request of the corresponding GII enzyme essential to lower the …”
Section: Discussionmentioning
confidence: 99%
“…Regarding tumorigenesis, RAGE and its ligands are commonly overexpressed in most types of solid tumors [18,[38][39][40][41][42][43][44][45][46][47][48]. For example, both amphoterin and RAGE are overproduced in inflammatory states, as well as in many malignant tumors with high metastatic capacity [42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…For example, both amphoterin and RAGE are overproduced in inflammatory states, as well as in many malignant tumors with high metastatic capacity [42][43][44][45][46][47][48]. However, a recent study showed that increased plasma AGE levels are associated with a protective effect over non-small cell lung cancer (NSCLC) tumor progression, presenting a simple predictor of patients' outcome after curative surgery [49].…”
Section: Introductionmentioning
confidence: 99%